The arduino SCADA training at the Mambaul Ulum Vocational High School, Gresik - Astutik, Rini Puji; Winarno, Hendra Ari; Eliyani, Eliyani; Irawan, Denny; Arifian, Raafi' Yanuar Purnama; Utomo, Muhammad Febri Prasetyo; Perdana, Adzriel Thoriq Helyo (Community Empowerment, 2021)
Students will be left behind in technological developments unless teachers in vocational schools constantly update their technical skills. One of such developments that is widely applied in the industry is the Supervisory Control and Data Acquisition (SCADA) application. This service aimed to share knowledge about SCADA technology with students of the Mambaul Ulum Vocational High School, Gresik in preparation for their entry into the industrial world. The results of the activity showed an increase in students' knowledge and mastery of Arduino which functions as a SCADA. This is further proven by the participants’ ability to solve the given case study.